Chemical compositions and pharmacological activities of natural musk (Moschus) and artificial musk: A review. (10th February 2022) - Lv, Shuquan; Lei, Zhixin; Yan, Ge; Shah, Sayed Afzal; Ahmed, Saeed; Sun, Taolei
Abstract: Ethnopharmacological relevance: Natural musk (Moschus), derived naturally from male musk deer ( Moschus berezovskii Flerov, Moschus sifanicus Przewalski, or Moschus moschiferus Linnaeus), has long been an important component of traditional Chinese medicine (TCM), and was used as resuscitation, blood circulation, and collateral drainage. detumescence and pain relief. Artificial musk was researched and applied into TCM as natural musk being as unsustainable resources. Aim of the study: We mainly summarized chemical compositions, pharmacological activities and mechanism of action of natural and artificial musk, and designed to serve as a foundation for further research into musk chemical compositions and pharmacological effect. Materials and methods: Those mainstream scientific databases including Google Scholar, ScienceDirect, SpringerLink, CNKI, Wiley Online Library, web of science, were used for searching with below "Keywords", as well as literature-tracking. Literatures spanned 1962 to 2021, and involved into Chinese, English, Janpanese, Korean. Results: Natural musk contains some very desirable but scarce compounds, as well as their biological features, which led to the development of artificial musk. The chemical ingredients, pharmacological activities, and mechanisms of action of natural and artificial musk are summarized and compared in this paper. Polypeptide and protein, muscone, musclide, steroids, muscopyridine, and other chemical constituents of musk demonstrated important therapeutic properties against inflammation, immune system disorders, neurological disorders, cardiovascular system disorders, and so on. The mechanism of action contributed to effect on mediators, acceptors and relative signal pathways. Conclusions: Natural and artificial musk were revealed having some activated compounds, and showed excellent pharmacological effect. Meantime, above two sides of natural and artificial musk ought to get further research. Graphical abstract: Image 1 Highlights: Natural musk and artificial musk was listed and compared for description of chemical compositions and pharmaceutical activities. Mechanisms of action in musk were summarized and analyzed among antiinflammation, neurological action and cardiovascular action. Give a recapitulative reference and enlightenment for future research.